Paparan Pestisida Organofosfat terhadap Kadar Kolinesterase Pada Saat Penyemprotan - Sari, Hendrika Puspita; Suhartono, Suhartono; Raharjo, Mursid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to assess exposure to organophosphate pesticides with cholinesterase levels based on articles published in national and international journals. The research method used is a systematic review via the journal sites Google Scholar, Garuda, Science Direct, Proquest, Scopus, JSTOR, and PubMed. The research results show that 14 research articles show that exposure to organophosphate pesticides can affect cholinesterase levels. Several factors support the occurrence of this poisoning, namely behavior when spraying, use of PPE, length of work, and frequency of spraying. In conclusion, factors related to cholinesterase levels include behavior when swelling, use of PPE, size of work, and frequency of spraying. Keywords: Cholinesterase Level, Organophosphate